Benefits of Caregiver Preparedness to Maintain Quality of Life In Caring for Stroke Patients: A Literature Review. - Supriadin, Supriadin; III Dioso, Regidor; Saifulaman Mohamed Said, Mohamed; Che Hassan, Hafizah (Journal of Neonatal Surgery, 2025)
Introduction: Stroke can cause neurological impairment that impacts a person's quality of life. Quality of life includes mental, physical, and social health. To achieve optimal quality of life, support from family and health workers is very important. Caregiver readiness in stroke patients is the preparation made by caregivers to accompany patients during the care process in order to support healing and improve their health status. Objectives: This literature review aimed to understand how caregiver preparedness can improve their quality of life when caring for stroke survivors. Methods: This study phase began with selection based on the year of publication and availability of full text. Subsequently, articles and journals deemed less relevant were excluded from the list. The literature used in this study was drawn from 10 relevant articles, which were obtained through Google Scholar with keywords such as "Benefits", "Nurse Preparedness", "Quality of Life", "Caring", and "Stroke". " Results: After reviewing the selected articles, it was found that caregiver preparedness positively impacts family readiness in caring for stroke patients. The family readiness also contributes to improving the quality of life of stroke patients. Some factors that play an important role in this include the moderating role of caregiver preparedness, togetherness, and benefits obtained among family caregivers of stroke patients. In addition, caregiver burden and experience, dyadic psychoeducational interventions for stroke patients and caregivers, and the support provided to caregivers also greatly affect success in caring for stroke patients. However, there was one study that showed a negative relationship, namely the experience of caregiver fatigue in caring for stroke patients. The high level of need for stroke patients causes the caregiver's burden to increase and results in a decrease in the caregiver's quality of life. Therefore, caregiver readiness is needed in caring for stroke patients, which can ultimately improve rehabilitation activities, prevent disease complications, and increase compliance in taking medication and undergoing routine controls. Conclusion: Improving quality of life for stroke patients' caregivers is important, as this can support rehabilitation activities, prevent disease complications, and ensure patients adhere to medication and regular check-up schedules.